(untitled) (Vietnam Journal of Community Medicine, 2022)
Background: Female sexual dysfunction has only been studied from a modern perspective for more than six decades and is evolving rapidly [1]. “Female hypoactive sexual desire disorder” was first reported in the DSM-III 41 years ago [2], however, so far the understanding of physiology, pathogenesis, diagnosis, and treatment is still limited. Aim: To develop an overview of the diagnosis, approach, and treatment of female hypoactive sexual desire disorder. Methods: Synthesis and analysis of studies on female hypoactive sexual desire disorder and the latest guidelines on diagnosis and treatment of the International Society for the Study of Women’s Sexual Health, the International Consultation on Sexual Medicine, The International Society for Sexual Medicine. Results: Complete an update on the diagnosis and treatment of female hypoactive sexual desire disorder. Conclusions: The Decreased Sexual Desire Screener is essential to screen for female hypoactive sexual desire disorder. Asking about the disease, and exploiting psychological, physiological, relationship, and social factors are extremely important for diagnosis and treatment orientation. The treatment of female hypoactive sexual desire disorder may engage both psychosocial and biological strategies. This review aims is to develop an overview of the diagnosis, approach, and treatment of female hypoactive sexual desire disorder.